Microscope methods for observation of the phylloplane flora - Hallett, I.C.; Boyd-Wilson, K.S.H.; Everett, K.R. (New Zealand Plant Protection, 2010)
Microscopebased observation of surface microbes can support indirect techniques such as culturing or DNA analysis of surface washings by illustrating microbial distribution patterns interrelationships and the presence of unculturable or nonrecovered organisms Comparisons have been made between techniques of contrasting complexity For example surface replicas of the leaf made from transparent materials and scanning electron microscopy (SEM) were compared for their ability to present an accurate picture of the leaf surface and microbial populations Environmental SEM (ESEM) and cryoSEM minimise change and provide the most realistic and detailed images of the surface but have logistical difficulties Conventional critical point dried SEM samples even with extra processing and some physical change usually provided similar results and had advantages in handling The simpler replica techniques retained microbial number and distribution when compared to ESEM but were poor with rough surfaces Microbial material on replicas could be stained or labelled with antibodies to improve identification